(untitled) (TERRA LATINOAMERICANA, 2024)
Currently, agricultural activity is constantly threatened by the ef fects of climate change and radical expression of environmental factors as irregular rainfall distribution responsible for water availability and deficit. These factors generate water stress in productive systems, whose negative ef fect is reflected on morphological, physiological and biochemical aspects of vegetative growth. The use of biostimulants arises as a strategy to counteract this impact, improving crop ef ficiency in the use of resources and generating responses, as metabolite production, among other substances that mitigate the ef fects of oxidative stress. In this context, waxes, hydrogen peroxide (H2O2), salicylic acid (SA) and ALGAENZIMSMR were used on raspberry plants subjected to moderate water stress (-0. 8 MPa) to evaluate the fruit response in aspects of vegetative growth, physiological and biochemical quality. For the establishment, a completely randomized design was used with 5 treatments: Green Cover as 5 mL L-1, H2O2 10-4 M, salicylic acid 0.27 mM, ALGAENZIMSMR 7.5 mL L-1 and the control with 50% recovery of the transpired volume as well as water potential similar to the rest of plants and 4 replicates. The results showed that waxes, SA and algal extract increased the photosynthetic rate; the four treatments increased root length; waxes increased root height; and H2O2 increased root biomass. Compared to the control, higher levels of vitamin C and anthocyanins were produced in fruits – a very important aspect due to the functionality of these compounds in human health. Therefore, the use of these biostimulants are a very useful tool for crop management in environments with water restriction.